In situ boro-mullite phase formation in Glass-Ceramic glazes: Anatase-rutile phase transformations and microstructure properties - Taskiran, Fahriye; Kalpakli, Yasemen (ELSEVIER SCI LTD, 2024)
'' Boro-mullite is the name for mullites produced through the synthesis of boron-rich material and playing a critical role in producing high-performance materials. Also, the stability of the anatase phase in the glaze and against temperature has been addressed and improved by many studies. In situ boro-mullite crystals generated using various glass-ceramic glaze compositions that contain TiO2 and their impact on the transformation of anatase into a rutile phase were examined in this study. Additionally, the samples' water absorption, bulk density, apparent porosity and shrinkage, Vickers hardness, and optical properties were evaluated at various Al2O3 and B2O3 amounts at 700 degrees C, 800 degrees C, 900 degrees C, 1000 degrees C and 1100 degrees C. X-ray diffraction analysis revealed that as the temperature and Al2O3 ratio rose, it triggered the boro-mullite phase formation. On the other hand, increasing the Al2O3 ratio led to a rise in the samples' sintering temperature and delayed the anatase to rutile phase transformation. Furthermore, the presence of corundum crystals retarded the anatase crystal size growth during the remodelling process of the conversion of anatase to rutile. While the increase in the B2O3 ratio sharpened the peaks of albite crystals, the formation of rutile crystals accelerated with the increase in temperature and caused inhibition of albite formation. The albite phase's presence facilitated the creation of the liquid phase and achieved the 0.010 % water absorption and 0 % apparent porosity values as well the highest bulk density and microhardness with 2.476 g/cm3 and 550 H V. The yellowness (+b*) values were found to be the highest at 1100 degrees C where the rutile crystals reached their maximum size. The anatase-rutile conversion is postponed and the increase in the yellowness value is prevented by the glaze's formation of boro-mullite. FESEMEDS analysis showed that the temperature was the driving force in the transformation of acicular boro-mullite crystal into highly acicular prismatic needle crystal and spherical anatase crystals into the rod shape rutile.
Keywords: Titanium dioxide; Boro-mullite; Crystallite size changes; Glass ceramics; CRYSTALLIZATION; TIO2; TEMPERATURE; STABILITY; MECHANISM; MORPHOLOGY; COMPOSITE; EVOLUTION; PORCELAIN; PRODUCTS; Materials Science